Uso de agregados de rochas calcárias para camadas de pavimentos estabilizadas granulometricamente - Lima, Felipe Cordeiro de (2015)
Paving works require a great demand for materials, mainly to be used in granular layers of pavements.In many cases, the available materials do not provide suitable characteristics for use, if necessary, therefore, the application of techniques to improve their characteristics, or even carry out the search for new materials in other regions.In this sense, this research objectives to study the particle size stabilization of a local soil from the addition of limestone aggregates for use in granular layers of pavements.The soil is classified as a sandy soil and has low plasticity.The limestone aggregate presents all the fractions in its composition, with the predominance of coarse fraction, and low resistance. Accord in to the results of particles size distribution of soil and limestone aggregate it was determined the proportion of each material in the soil-aggregate mixtures.For this, the C and D particle size ranges for well graded stabilized bases from DNIT were considered.The mixtures were determined in three scenarios with addition of soil 25%, 50% and 75% limestone aggregates in relation to their mass.The results carried out increasing coarse soil fractions and decreasing of plasticity, as the aggregate content in the mixture was increased. With respect to mechanical properties, California Bearing Ratio, resilience modulus and compressive strength carried out for the mixtures were bigger than the soil and the limestone aggregate.In all mechanical tests, the best results were carried out for mixtures consisting of 50% soil and 50% aggregates, provided by biggest stability in function of particles rearrangement.That way, it can be concluded that the sandy soil and limestone aggregates mixtures can be used in sub-base layers for paving.